Monitoring of cerebral oximetry during head-up tilt test in adults with history of syncope and orthostatic intolerance. Issue 9 (28th September 2017) - Bachus, E; Holm, H; Hamrefors, V; Melander, O; Sutton, R; Magnusson, M; Fedorowski, A
Abstract: Aims : We applied near-infrared-spectroscopy (NIRS) to measure absolute frontal cerebral tissue oxygen saturation (SctO2) during head-up tilt test (HUT) in patients investigated for unexplained syncope. Methods and results : Synchronized non-invasive beat-to-beat haemodynamic monitoring, ECG, SctO2 (NIRS; normal range: 60–80%), and peripheral oxygen saturation (left hand, SpO2) were applied during HUT in a random sample of patients with unexplained syncope. Tracings of 54 patients (mean-age: 55 ± 19 years, 39% male) with negative HUT, vasovagal syncope (VVS), or orthostatic hypotension (OH) were analysed. In 44 patients HUT was diagnostic, in 10 HUT was negative. Thirty-one experienced VVS. Of these, 6 had spontaneous and 25 nitroglycerin-induced syncope. Thirteen patients had orthostatic hypotension (OH). Although there was no significant change in mean-arterial pressure from baseline to 1 min before syncope or end of passive HUT phase (−1.4 ± 13.9 mmHg; P = 0.45), there was a significant fall in SctO2 during the same period (−3.2 ± 3.2%; P ≤ 0.001). Among patients who experienced syncope, a decrease in SctO2 from 71 ± 5% at baseline to 53 ± 9% ( P < 0.001) at syncope was observed. During HUT, there was a significant difference in delta SctO2 between spontaneous VVS (−4.5 ± 3.0%) and negative HUT (−1.3 ± 1.9%; P = 0.021), but not between spontaneous VVS and OH (−5.4 ± 4.2%; P = 0.65). In spontaneous VVS, progressive decrease of SctO2 was independent of mean arterial pressure decrease ( P = 0.22). Conclusions: Progressive decrease in cerebral tissue oxygenation independent of mean-arterial pressure may precede spontaneous vasovagal reflex during tilt. Patients experience syncope when SctO2 falls below 60%. These data confirm clinical utility of absolute cerebral oximetry monitoring for syncope investigation. We applied NIRS to measure frontal cerebral tissue oxygen saturation (SctO2) during head-up tilt test (HUT) in patients with unexplained syncope. In 44 of 54 patients, HUT was diagnostic. In patients with syncope, a significant SctO2-decrease was observed. Different patterns of SctO2 can be detected.